1997
DOI: 10.1016/s0741-5214(97)70348-3
|View full text |Cite
|
Sign up to set email alerts
|

The factor V Leiden mutation: Spectrum of thrombotic events and laboratory evaluation

Abstract: The factor V mutation is a common cause of venous thromboses but may also be associated with the early presentation of arterial thrombotic events. The APC resistance test is a sensitive screening assay but has limitations of its specificity in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 15 publications
0
24
0
1
Order By: Relevance
“…Since then, the terms APC-R and FVL were linked together and used interchangeably. Several studies quickly followed that discovery and proved a positive association between FVL and VTE, showing that heterozygous carriers of the mutation are at higher risk of developing VTE by 10-fold while homozygous carriers have a much higher risk ratio reaching 140-fold (Dahlbäck et al, 1993;Zöller et al, 1994;Bertina et al, 1994;Hoagland et al, 1996;Dahlbäck, 1997;Faioni et al, 1997;Alderborn et al, 1997;Bontempo et al, 1997). Moreover, most homozygous cases were found to get at least one VTE event in their life time, and at an earlier time of their life (Samama et al, 1996;Florell & Rodgers, 1997).…”
Section: Activated Protein C Resistance (Apc-r) and Factor V Leiden Mmentioning
confidence: 99%
“…Since then, the terms APC-R and FVL were linked together and used interchangeably. Several studies quickly followed that discovery and proved a positive association between FVL and VTE, showing that heterozygous carriers of the mutation are at higher risk of developing VTE by 10-fold while homozygous carriers have a much higher risk ratio reaching 140-fold (Dahlbäck et al, 1993;Zöller et al, 1994;Bertina et al, 1994;Hoagland et al, 1996;Dahlbäck, 1997;Faioni et al, 1997;Alderborn et al, 1997;Bontempo et al, 1997). Moreover, most homozygous cases were found to get at least one VTE event in their life time, and at an earlier time of their life (Samama et al, 1996;Florell & Rodgers, 1997).…”
Section: Activated Protein C Resistance (Apc-r) and Factor V Leiden Mmentioning
confidence: 99%
“…[1][2][3][4][5][6] It is present in a high number of Caucasians, 1,4,6,7,[10][11][12][13][14][15][16][17][18][19][20] but it is very rare in other ethnic groups. 7,17,[20][21][22][23][24][25] Few studies on Arabs showed that the prevalence of FVL was 0-27% in different Arabic countries, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] being as low as zero in countries like Saudi Arabia, 7,29,40 Oman 34 and Yemen, 27 whereas being relatively very high (27%) in Palestinians (Israeli Arabs).…”
Section: Delta Rnmentioning
confidence: 99%
“…3,4,7,8 Studies have shown that people with FVL had a higher risk of developing VTE (10-fold and 140-fold increased risk in heterozygous and homozygous carriers, respectively). 1,2,5,6,[9][10][11][12] Several studies were conducted worldwide to determine the prevalence and risk of FVL in different countries and ethnic groups. FVL was reported to be highly present in populations of Caucasian origin living in Europe, United States and Australia, with a prevalence of 15-65% among VTE patients and 1-15% in the normal populations studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most common genetic cause of a prothrombotic phenotype is the factor V Leiden mutation in which one nucleotide change at position 1691 of the gene results in the substitution of adenine for guanine in the structure of factor V. 5,6 This mutation results in a delay in the inactivation of activated factor V. 5 It is present in approximately 5% of the US population and increases the risk of venous thrombosis three-fold to eight-fold for heterozygous carriers 7-10 and 80-fold for homozygous carriers. 8 The factor V Leiden mutation also has been linked to a variety of arterial events.…”
mentioning
confidence: 99%